2015
DOI: 10.1186/1944-3277-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of Mesotoga strain PhosAC3, a mesophilic member of the bacterial order Thermotogales, isolated from a digestor treating phosphogypsum in Tunisia

Abstract: Mesotoga strain PhosAc3 was the first mesophilic cultivated member of the order Thermotogales. This genus currently contain two described species, M. prima and M. infera. Strain PhosAc3, isolated from a Tunisian digestor treating phosphogypsum, is phylogenetically closely related to M. prima strain MesG1.Ag.4.2T. Strain PhosAc3 has a genome of 3.1 Mb with a G+C content of 45.2%. It contains 3,051 protein-coding genes of which 74.6% have their best reciprocal BLAST hit in the genome of the type species, strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Growth on acetate was reported for Mesotoga PhosAc3 (Hania et al ., ), and we observed weak stimulation of growth of its close relative M. prima by acetate (day 5–10 in Supporting Information Fig. S4 and Supporting Information Table S6).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Growth on acetate was reported for Mesotoga PhosAc3 (Hania et al ., ), and we observed weak stimulation of growth of its close relative M. prima by acetate (day 5–10 in Supporting Information Fig. S4 and Supporting Information Table S6).…”
Section: Resultsmentioning
confidence: 84%
“…The first described member of this genus, Mesotoga prima MesG1Ag4.2 (hereafter, M. prima ), was isolated from a PCB‐degrading enrichment culture inoculated with sediments from Baltimore Harbour, Maryland (USA) (Nesbø et al ., ; ). Sequencing the genomes of M. prima and the very closely related M. prima PhosAc3 (hereafter, PhosAc3) isolated in Tunisia (Hania et al ., ) revealed larger genomes than in thermophilic Thermotogae, with more genes involved in regulatory functions and interactions with the environment (Zhaxybayeva et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The same conclusion may be drawn for M. prima strain PhosAc3 since, similarly as for Müller et al . (), it has been isolated after high dilution steps from anaerobic digester treating phosphogypsum (Ben Hania et al ., ). It may be extended to other Mesotoga strains which have been detected by molecular approaches in various ecosystems including those contaminated by toxic compounds (Nesbø et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The first described member of this genus, Mesotoga 63 prima MesG1Ag4.2 (hereafter, M. prima), was isolated from a PCB-degrading 64 enrichment culture inoculated with sediments from Baltimore Harbor, Maryland (USA) 65 (Nesbø et al, 2006;. Sequencing the genomes of M. prima and the very closely 66 related M. prima PhosAc3 (hereafter, PhosAc3) isolated in Tunisia (Hania et al, 2015) 67 revealed larger genomes than in thermophilic Thermotogae, with more genes involved in 68 regulatory functions and interactions with the environment (Zhaxybayeva et al, 2012). 69…”
Section: Originality-significance Statement 24mentioning
confidence: 99%
“…Colorado USA (TOLDC). We also included in our analyses the draft genome of PhosAc3, 116 previously isolated in Tunisia (Hania et al, 2015) 139 Very little reticulate evolution was observed among the three groups ( Fig. 1b), 140 and the A lineage in particular showed very little connection with the other two groups, 141 suggesting that the three lineages have evolved independently for a relatively long time.…”
Section: Genome Sequences 108mentioning
confidence: 99%